tom-1, a novel v-Myb target gene expressed in AMV- and E26-transformed myelomonocytic cells. - Burk, O (1997)
The retroviral oncogene v-myb is a mutated and truncated version of the c-myb proto-oncogene and encodes a transcription factor (v-Myb) that specifically transforms myelomonocytic cells. Two different variants of v-myb, transduced independently by the oncogenic chicken retroviruses AMV and E26, have been characterized. It is believed that both variants of v-Myb transform myelomonocytic cells by affecting the expression of specific genes; however, no target genes common to both oncogenic viruses have been identified. Here, we describe the identification of a novel v-Myb target gene, designated as tom-1 (target of myb 1). The tom-1 gene has two promoters, one of which is Myb-inducible. tom-1 is expressed at elevated levels in AMV-transformed as well as in E26-transformed myeloid cells. We show that tom-1 activation by v-Myb does not require de novo protein synthesis and that the Myb-inducible tom-1 promoter contains a functional Myb binding site. Thus, tom-1 is the first example of a direct target gene for both oncogenic forms of the v-myb gene. Further analysis of the Myb-inducible tom-1 promoter shows that a C/EBP binding site is juxtaposed to the Myb binding site and that C/EBP is required for the Myb-dependent activation of the promoter. Together with previous work our results suggest that C/EBP may be a general cooperation partner for v-Myb in myelomonocytic cells.